Diversidade sexual e de gênero nas relações de trabalho: afirmar direitos e promover inclusão - Abílio, Adriana Galvão Moura (2019)
In this thesis, we propose an analysis of the recognition of the rights of sexual and gender diversity in labor relations, in an approach to the effectiveness of legal protection against discrimination of LGBT people in work relations. The need to improve Brazilian legislation with the approval of law projects such as the Statute of Sexual and Gender Diversity, as well as propose means and affirmative action for efficient inclusion of sexual and gender diversity into the labor market. Sexuality has a primary role in the construction of one’s individuality, establishing an indispensable foundation for the free development of their characters and the recognition of their sexual condition and individuality. In the specific case of the work environment, LGBT people, without detriment to others, hold the protection of human dignity and the right to a harmonious working environment that should respect differences and combat any discriminatory actions and attitudes. Understanding the real need of business organizations to adopt measures to balance rights and respect diversity in corporate environments is linked to the fulfillment of corporate social responsibility and duty, in a dynamic process of building a more inclusive society that recognizes, in fact, the vulnerabilities of LGBT employees as a way of implementing projects and actions aimed at guaranteeing the fundamental right to work as a social and human right. The choice of the topic is justified because social reality presents a real scenario for LGBT people, especially the transvestite population, transsexual women and men who are excluded from the formal labor market, due to the absence of compensatory actions that propose practical and effective measures of inclusion. The objective of the present work is to raise important questions regarding the human rights violations of LGBT people in the work environment, identifying the difficulty of access and permanence in a context of the analysis of concrete cases, besides exposing a survey of legal instruments domestic and international as a way to ensure the protection of these people. The theme of the rights of sexual and gender diversity in work relations as a way of expanding rights and promoting inclusion deserves to be discussed and confronted, even in the face of all the challenges that the theme and its related subjects propose, as our commitment as researchers is to develop this theme as a way to contribute to the recognition of the rights of LGBT workers, in addition to demonstrating the commitment of companies to respect Human Rights as a paradigm for accomplishing their role and social responsibility. The main method of research is based on the bibliographic review, through an analysis of the literature on this subject, in order to portray a theoretical framework and structure concepts of support and development for the research